USING CONCEPT MAP SOFTWARE TO IMPROVE SUMMARY WRITING QUALITY - Muhammad Nadjmuddin; Eli Yeny; Sunani -; Herman - (HOLISTICS, 2017)
This study suggests that conceptual summarizing of multiple sources is key to deep learning and useful to language learning strategies. The participants of this study were 68 students from three classes studying in upper intermediate reading course at English Department of State Polytechnic of Sriwijaya in Palembang. The t test indicated that the students who received strategic summarizing intervention in this study received significantly higher marks after eight reading and summarizing measures using computer based concept map. Collected data from questionnaire and focus group discussion showed that during summarizing from multiple sources using computer-based concept map the students employed prereading, conceptual reading and summarizing strategies. We could note the student activities which stressed the various aspects of conceptual learning. It is suggested that conceptual summarizing of multiple sources using computer-based concept map is used in English reading because it allows students to process information from sources, without which they are not able to organize main ideas into a coherent summary. It also facilitates students to become familiar with the textual structure of English academic summary writing.